Nutritional counseling in childhood and adolescence: a systematic review - Neri, Lenycia de Cassya Lopes; Guglielmetti, Monica; Fiorini, Simona; Quintiero, Federica; Tagliabue, Anna; Ferraris, Cinzia (Frontiers in Nutrition, 2024)
Healthy eating habits are the basis for good health status, especially for children and adolescents, when growth and development are still ongoing. Nutrition educational programs are essential to prevent and treat chronic diseases. Nutritional counseling (NC), as a collaborative process between the counselor and the client process, could help to achieve better outcomes. This review aims to collect information about the utilization of NC during childhood and adolescence and to highlight its possible impact on adherence/compliance rates, nutrition knowledge, status and dietary intake. The methods applied in this systematic review followed the instruction of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The search in PubMed/Medline, Scopus, Web of Science, LILACS, and Science Direct included observational or randomized studies. RoB 2.0 and Robins-I tools was used for the risk of bias assessment in randomized and non-randomized studies, respectively. The quality of evidence was checked by the Mixed Methods Appraisal Tool system. A total of 21 articles were selected, computing 4,345 individuals. 11 achieved at least 4 stars quality level. The highest risk of bias for randomized studies was related to the randomization process. 42.9% of non-randomized studies had some concerns of bias, mainly because of a lack of control of all confounding factors. Different strategies of NC were used in children and adolescents with positive results for health or diseases. NC strategies can be effectively used in children and adolescents. In general, NC showed benefits in pediatrics age for anthropometric or body composition parameters, dietary intake, nutrition knowledge and physical activity improvement. Performing NC in pediatrics is challenging due to the counseling strategies that must be adapted in their contents to the cognitive ability of each age. More structured research must be done focused on this population. Investments in healthy eating behaviors in pediatrics can lead to better health outcomes in the future population with substantial benefits to society. Systematic review registration [https://www.crd.york.ac.uk/prospero/#recordDetails], identifier [CRD42022374177].